Determinación del porcentaje biorremediador del Bocashi, en suelos contaminados por glifosato Mediante la técnica de biolabranza en cultivos Asociados de café y cacao en el barrio san roque, Parroquia pachicutza, cantón el pangui, provincia Zamora chinchipe - Llivichuzca Lojano, Grey Fernanda (2016)
The contamination of soils constitutes one of the serious problems that threaten the physical-chemical and biological properties of the soil that determine the sustainability of the same, putting at risk the quality of the food and consequently the food sovereignty of the population. As an alternative to solving this problem, the present project proposes the Biolabranza in combination with bocashi, which is important for the remediation of soils, as the tillage promotes the aeration and therefore the proliferation of microorganisms that degrade pollutants in the medium and long term. This research work was done in the San Roque neighborhood of Pachicutza parish, canton El Pangui. In synthesis this project consists of two treatments distributing them as follows; treatment one (100kg of contaminated soil and 50 kg of bocashi) and treatment two (80kg of contaminated soil) with one repetition for each treatment. Where as a results it was obtained that the application of the bocashi fertilizer, significantly improved the parameters; Phosphorus, organic matter, nitrogen, Ph, potassium, and that there was a 90% removal efficiency of the glyphosate contaminant that is from 0,5 mg/kg to 0,05 mg/kg. It is worth mentioning that treatment one presents better results in terms of decontamination and improvement of is fertility.